Exploling the Scientific Model for Constructing a Platform for the International Communication of PingJiang Opera - Wu, Jing-jing; Dang, Weibo (Journal of Ecohumanism, 2024)
Purpose: Considerable changes have occurred in many areas of science and technology as a result of the current information technologies' quick development and use. Specifically, new theories in mathematics have surfaced; they may be used to construct and refine current mathematical models of different processes and objects. Method: Regulatory and permitting decision-makers are worried about the ambiguity surrounding the possible environmental consequences arising from the introduction of these innovative devices in coastal and riverine ecosystems as research and testing of maritime energy devices progress. The Triton Initiative conducts studies and makes suggestions for environmental monitoring techniques and technology to give industry stakeholders with the information required to approve maritime energy system testing. Results: The efficient distribution of research findings is crucial in enhancing data accessibility for stakeholders who might use the information to make informed policy choices. Nevertheless, there are few frameworks available for carrying out scientific communications related to marine energy projects. Using the Triton Initiative's pilot scientific communication program as a case study, we discuss methods, resources, and strategies for creating a science communication framework for marine energy projects or other related fields of research in this article. Conclusion: This article uses the historic Pingjiang Road in Suzhou, China, as a case study to investigate how, in the era of globalization and digital media, urban spaces that have been revitalized for historic and cultural consumption may demonstrate the publicness or potential capacity for publicity.